PENINGKATAN FUNGSI BENDUNG PLUMBON-SEMARANG SEBAGAI PENGENDALI BANJIR - Danang Dwi Admojo; M. Kurnia Hermawan; Salamun Salamun; Dwi Kurniani (Jurnal Karya Teknik Sipil, 2015)
Flood happened recently is already a thing happened each time in various regions in Indonesia, not least in Semarang, especially in the area Mangkang. Improved function of the weir Plumbon previously only built for irrigation becomes a flood control dam is expected to reduce or cope with floods that occur each year in these areas. Plumbon river has a total length of 14.123 km with the average slope of the river (i) 0.0165. Plumbon watershed has an area of 20.36 km2. Planning weir Plumbon increased functionality using rainfall data of the last 12 years (2002 - 2014) with 3 stations namely rain Middle Reef (33F), Mangkang Reservoir (41C), Kaligading (20). Calculation of flood discharge plan obtained with a return period of 20 years (Q20) of 365.015 m³ / s with HSS method Gama I. Enhanced functions for flood control is done by raising the dam height lighthouse, so the catchment area will increase and may decrease the discharge passing through the dam , Plumbon weir using high lighthouse beacon round with 8 m wide and 17 m effective. Plumbon weir is planned to advance along the floor of 9.0 m and use a pool megrim with length of 16.5 m with a thickness of 2.5 m pool floor megrim selected while the pool is the type USBR type III.